A comparative review of intelectins. (14th April 2020) - Chen, Lei; Li, Jinyi; Yang, Guiwen
Abstract: Intelectin (ITLN) is a new type of glycan‐binding lectin. It has been demonstrated to agglutinate bacteria probably due to its carbohydrate‐binding capacity, suggesting its role in an innate immune response. It is involved not only in many physiological processes but also in some human diseases such as asthma, heart disease, inflammatory bowel disease, chronic obstructive pulmonary disease and cancer. Up to now, intelectin orthologs have been identified in placozoans, urochordatas, cephalochordates and several vertebrates, such as cyclostomata, fish, amphibians and mammals. Although the sequences of intelectins in different species are conserved, their expression patterns, quaternary structures and functions differ considerably among and within species. We summarize the evolution of the intelectin gene family, the tissue distribution, structure and functions of intelectins. We conclude that intelectin plays a role in innate immune response and there are still potential functions of intelectin awaiting discovery.